Вы находитесь на странице: 1из 12

Question 1- Solve the system of equation by matrix inversion

method
x+y+z=1
x + 2y + 3z = 6
x + 3y + 4z = 6
Answer:
The given equation can be written as
AX=B
X => A-1 B

(*)

Where

B=

Det

= 1(8 - 9) 1 (4 - 3) + 1 (3 2) = -1 0

A-1 exists
A-1 =

1
adj A
det A

First let us find adj. A


Cofactor of a11 = 1 = (-1) 1+1
Cofactor of a12 = 1 = (-1) 1+2
Cofactor of a13 = 1 = (-1) 1+3
Cofactor of a21 = 1 = (-1) 2+1
Cofactor of a22 = 1 = (-1) 2+2
Cofactor of a23 = 1 = (-1) 2+3
Cofactor of a31 = 1 = (-1) 3+1
Cofactor of a32 = 1 = (-1) 3+2
Cofactor of a33 = 1 = (-1) 3+3

ROLL # 1505007223 BCA 3010

Cofactor of A =

Adjoint of A
A-1 =

1 1 1
1 3 2

1 2 1

1 1 1
1 3 2

1 2 1

1 1 1
1 3 2

1 2 1

1
1
adj A=
det A
1

1 1
1
1 3 2

1 2 1

So from (*) we have

X=

1 1 1 1
1
1 3 2 6 5

1 2 1 6 5

ROLL # 1505007223 BCA 3010

Question 2- Find all eigen values and the corresponding eigen


vectors of the matrix
8 6 2
6 7 4

2 4 3
A=
Answer:

| AI |=0
The characteristic equation of A is
8 6
6 7

That is

2
4
3

where

0 0
0 0

0 0

Expanding we get

(8 -

That is,

)[(7- )(3- ) 16 ] + 6 [ -6 (3- ) + 8] + 2 [24 2 (7- )] = 0

+ 18
3

Therefore,

+ 18
- 3) (

45
2

45

=0

= 0 on simplification.

- 15) = 0

= 0, 3, 15 are the eigen values of A.

If x,y,z be the components of an eigen vector corresponding to the eigen


value

(A -

, the we have

8
6

I) X =

2
4

7
y

4 3 z

ROLL # 1505007223 BCA 3010

0
0
0

That is,
(8- ) x 6y + 2z

= 0

-6x + (7- ) y 4z = 0
2x 4y + (3-)z

= 0

Case I: Let = 0 we have


8x 6y + 2z
-6x + 7y 4z
2x 4y + 3z

= 0
= 0
= 0

(i)
(ii)
(iii)

Applying the rule of cross multiplication for (i) and (ii)


x
6

y
8

6 4

z
8

x
y
z

24 14 32 12 56 36
x
y
z
x y z

or
10 20 20 1 2 2

Therefore (x, y, z) are proportional to (1, 2, 2) and we can write x = 1k, y =


2k, z = 2k where k ( 0) is an arbitrary constant. However it is enough to
keep the values of (x, y, z) in the simplest form x = 1, y = 2, z = 2 (putting k
= 1). These values satisfy all the equations simultaneously.

Thus the eigen vector X1 corresponding to the eigen value = 0 is


Case II: Let = 3 and the corresponding equations are
5x 6y + 2z = 0
6x + 4y 4z = 0
2x 4y = 0

1

2
2

(iv)
(v)
(vi)

From (iv) and (v) we have


x
6 2
4 4

y
5
2
6 4

z
5 6
6 4

ROLL # 1505007223 BCA 3010

That is,

That is,

x y
z

16 8 16
x y
z

2
1
2

Thus X2 =

1
2

is the eigen vector corresponding to = 3

Case III: Let = 15 and the associated equations are


-7x 6y + 2z = 0
6x - 8y 4z = 0
2x 4y - 12z = 0

(vii)
(viii)
(ix)

From (vii) and (viii) we have


x
y
z

40 40 20

That is,

x
y
z

2 2 1

2
Thus X3 =

is the eigen vector corresponding to = 15.

There for = 0, 3, 15 are the eigen values of A, and


the corresponding eigen vectors.

ROLL # 1505007223 BCA 3010

1

2
2

1
2

and

2
1

are

Question 3- Find the cubic polynomial which takes the following


values y(0) = 1, y(1) = 0, y(2) = 1 and y(3) = 10. Hence or
otherwise, obtain y (0.5)
Answer:
Here x0 = 0, x1 = 1, x2 =2, x3 = 3 and y0 = 1, y1 = 0, y2 = 1, y3 = 10.
We form the difference table
x
x0 =
x1 =
x2 =
x3 =

y
y0 = 1
y1 = 0
y2 = 1
y3 = 10

0
1
2
3

y0 = -1
y1 = 1
y2 = 9

2y0 = 2
2y1 = 8

3y0 = 6

From the above table we have


X0 = 0, y0 = 1, y0 = -1, 2y0 = 2, 3y0 = 6
Using Newton forward difference formula
y ( x ) = y 0+ p y 0+

p( p1) 2
p ( p1 ) ( p2) 3
y 0+
+ y 0 where x =x0 + ph
2!
3!

Here h = 1, x0 = 0, therefore p = x
y ( x )=1+ x (1 )+

x ( x1 )
x ( x 1 )( x2 )
2+
6
1.2
1.2 .3

1x + ( x 2x ) + ( x 33 x 2+2 x )

y ( x )=x 3 2 x 2 +1
which is the polynomial from which we obtained the above tabular values.
To compute y(0.5)
Here x0 + ph = x = 0.5
p=0.5 since x0 =0h=1

1+ 0.5 (1 ) +

y ( 0.5 )= y 0 + p y 0 +

p ( p1 ) 2
p ( p1 )( p2 ) 3
y0 +
y0
2!
3!

( 0.5 ) ( 0.51 ) ( 0.5 ) ( 0.51 )( 0.52 )


2+
6
2
6

0.625

which is the same value as that obtained by substituting x = 0.5 in the cubic
polynomial.
ROLL # 1505007223 BCA 3010

ROLL # 1505007223 BCA 3010

Question 4 Find the approximate value of

cos

by Simpsons

1
rd
3

rule by dividing

[ ]
0,

into 6 equal parts.

Answer:
Here a = 0, b =

2 , n = 6,

0
ba 2

h=
=
= 15
n
6
12

Length of each part,

The values of

and the corresponding values of y =

cos correct to

four decimal place are tabulated.


0

12

2
12

3
12

4
12

5
12

6
12

y0

y1

y2

y3

y4

y5

y6

1.0000

0.9828

0.9306

0.8409

0.7071

0.5087

0.0000

y= cos

By Simpsons
6

1
rd rule
3

for n = 6 given by

yd = 3 [ ( y 0 + y 6 ) + 4 ( y 1 + y 3+ y 5 ) +2 ( y 2+ y 4 ) ]
0

cos d= 12x 3 [ ( 1+ 0 ) +4 ( 0.9828+0.8409+0.5087 )+ 2 ( 0.9306+ 0.7071 ) ]

1.1873

Therefore

cos d=1.1873
0

ROLL # 1505007223 BCA 3010

ROLL # 1505007223 BCA 3010

Question 5- Use Picards method of successive approximations to


y 1 , y 2 , y3

find

to the solution of the initial value problem

given that y = 2 for x = 0. Use

y3

'

y=

dy
=y,
dx

to estimate the value of y (0.8).

Answer:
On comparing

y'=

dy
=y,
dx

and

y 0=2, x 0=0

y 2= y 0 + f ( x , y 1 ) dx

2+ y 1 dx

to eq(1), we get

f ( x , y )= y

So first approximation will be


x

y 1= y 0 + f ( x , y 0 ) dx
x0

2+ y 0 dx

2+ 2 dx

2+2 ( x )0x

2+2 x

x0

x
0

2+ ( 2+2 x ) dx

2+(2+ x 2)0x =2+2 x+2 x 2

y 3= y 0 + f ( x , y 2 ) dx
x0

x
2
2+ ( 2+2 x +2 x ) dx
x0

x3
2+2 x +2 x +
3
2

At

x=0.8
3

(0.8)
y 3=2+2 ( 0.8 ) +( 0.8) +
=4.41
3
2

ROLL # 1505007223 BCA 3010

10

Question 6: Solve x

y +y=0, y' (1)=0, y(2)=1, h= {1} over {2}

Answer:
x 0=1, x 1=1.5, x 2=2
y 0= y ( x 0 )= y ( 1 )=?
y 1= y ( x 1) = y ( 1.5 )=?
y 2= y ( 2 )=1
y 0 =( y ' ( x0 ) )
'

We have
xi

y i +12 y i+ y i1
h2

+ y i =0

4 x i ( y i+12 y i + y i1 ) + y i=0 ( 1 )
Put

i=0 ( 1 ) ,

4 x 0 ( y 12 y 0 + y1 ) + y 0=0

Also,

y 'i=

y i+1 y i1
= y i+1 y i1
2h

Take i=0, we get,

y 0= y 1 y1

y1= y 1 y'0= y 1 ( since y '0=0 )


Therefore

4 ( y 12 y 0+ y 1) + y 0=0

8 y 17 y 0 =0 ( 2 ) Put i=1,

ROLL # 1505007223 BCA 3010

11

4 x 1 ( y 22 y 1+ y 0 ) + y 1=0
6 ( y 22 y 1 + y 0 ) + y 1=0
6 y 211 y 1 +6 y 0=0
11 y 1 +6 y 0 =6 (3 )

Solving (2) and (3),

y 0=

48
42
=1.6552, y 1= =1.4482
29
29

ROLL # 1505007223 BCA 3010

12